Vocational Guidance as a Predictor of Career Development in Higher Education and Vocational Education: A Systematic Literature Review - Chufadatul Chusna; Tuwoso; Hary Suswanto (Eduscape : Journal of Education Insight, 2026)
This study examines the role of vocational guidance as a predictor of career development within higher education and Technical and Vocational Education and Training (TVET) contexts. While its importance has increased, limited studies have synthesized its predictive role across diverse educational settings. This study employs a Systematic Literature Review (SLR) following the PRISMA framework, analysing 40 peer-reviewed journal articles published between 2019 and 2025, retrieved from Scopus, Web of Science, SpringerLink, DOAJ, and Google Scholar. A thematic synthesis approach was applied, involving coding, categorization, and theme development to identify patterns in research trends, impacts, moderating factors, and emerging guidance models. The findings indicate that vocational guidance is generally associated with improved career readiness, employability, and career outcomes; however, these effects are context-dependent and influenced by individual, institutional, and technological factors. The review also identifies a shift toward digital, hybrid, and work-integrated guidance models. This study contributes by positioning vocational guidance as a central predictor and systematically mapping moderating factors and emerging models within a unified analytical framework.